Power Quality Analysis of Vienna Rectifier for BLDC Motor Drive Application - K. Srinivasan; S. Vijayan; S. Paramasivam; K. Sundaramoorthi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents the power quality improvements for a BLDC driver using Vienna rectifier as front end converter. The major drawbacks in the BLDC motor drive and non linear load applications are the line pollution and depreciation of the power factor. The conventional power factor correction method is not economical and efficient. It requires bulky components as load changes and produce high THD and less Power factor. The front end converter of BLDC bridge inverter drive is proposed by the Vienna rectifier, which can contribute more significantly in improving the power factor and reduce the line pollution. The Vienna rectifier topology is controlled by the constant switching frequency control technique for wide range of load variation and it reduces the THD, improve the power factor and provide a steady DC link voltage to the bridge inverter to drive the BLDC motor. The design calculation and performance characteristics of BLDC motor and Vienna rectifier are verified by using Matlab simulation.